Understanding Pre-Service Teachers’ Conceptual Difficulties in Learning Newman Projections - Adlim, Muhammad; Syahrial, Syahrial; Winarni, Sri; Deriyani, Deriyani; Gani, Abdul; Rusman, Rusman; Salaeh, Subhan (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2025)
Challenges in mastering chemistry content among pre-service chemistry teachers remain a critical concern in teacher education institutions. This study aims to analyze the most difficult concepts and the underlying conditions contributing to students' failure in mastering specific chemistry courses. Data were collected through questionnaires, interviews, and document analysis. The research began by identifying courses with the highest proportion of failing grades (≤ D) based on academic transcripts from 235 students across four cohorts in a chemistry education program. Organic Chemistry I was identified as the course with the highest failure rate, affecting 141 students. From this group, ten students from each cohort with a GPA ≥ 3.0 were randomly selected to complete a questionnaire identifying the most difficult topics in the course. In-depth interviews with students and lecturers were then conducted to explore the conceptual difficulties and their possible causes. Findings consistently revealed that Organic Chemistry I had the highest proportion of D grades (10%) compared to other courses, with more than 60% of students in each cohort receiving low grades. Students reported that the Newman projection was the most challenging topic, citing both the abstract nature of the concept, which requires spatial reasoning and mental rotation of molecular structures, and the lack of effective instructional strategies to support understanding. These results highlight the need for pedagogical innovations targeting spatial visualization skills to enhance conceptual comprehension in organic chemistry education.